Contrary effects of coenzyme Q10 and vitamin E after testicular ischemia/reperfusion in a rat model validated with glucose metabolism imaging - AKDENİZ, ESRA (SAGE PUBLICATIONS LTD, 2021)
Objective: To evaluate the efficacy of antioxidants in cellular-level post-ischemia/reperfusion injury of the testis and to validate these effects with F-18-fluorodeoxyglucose positron emission tomography. Methods: Fifty-six adult male rats were randomly divided into seven groups-Group 1: sham; Group 2: ischemia/reperfusion only group; Group 3: ischemia was induced and vitamin E (100 mg/kg) was administered intraperitoneally 30 min before reperfusion; Group 4: vitamin E was given intraperitoneally without ischemia/reperfusion; Group 5: ischemia was induced and coenzyme Q10 (10 mg/body weight) was administered intraperitoneally 30 min before reperfusion; Group 6: coenzyme Q10 was administered intraperitoneally without ischemia/reperfusion; Group 7: ischemia was induced and coenzyme Q10 + vitamin E was administered intraperitoneally 30 min before reperfusion. After detorsion, fluorodeoxyglucose was applied to all groups according to the animals' weight and fluorodeoxyglucose positron emission tomography was performed after 1 h. In pursuit of imaging, orchiectomy was performed for histopathological and biochemical evaluations. Results: A significant effect of group on catalase, maximum standardized uptake value, and seminiferous tubule diameters (p < 0.005) was observed. According to this, combining ischemia/reperfusion with vitamin E increased the maximum standardized uptake value significantly higher than in all other groups; in addition, catalase was significantly higher than in Groups 4-6. Histopathological outcomes revealed that sham had significantly larger seminiferous tubule diameter than Groups 2-4. Also, ischemia/reperfusion was the only group which had significantly smaller seminiferous tubule diameters than Groups 6 and 7. Conclusion: In contrast to vitamin E, coenzyme Q10 provided remarkable regression of oxidative stress-induced enzymes and revealed consistent effects on histopathological outcomes, which were validated with fluorodeoxyglucose positron emission tomography imaging.
Keywords: Ischemia/reperfusion; testis; fluorodeoxyglucose positron emission tomography; coenzyme Q10; vitamin E; FDG-PET/CT; TORSION; ISCHEMIA; INJURY; TESTES; ANTIOXIDANTS; ALLOPURINOL